Sex-related differences in sternocleidomastoid muscle morphology in healthy young adults: A cross-sectional magnetic resonance imaging measurement study. (October 2022) - Migotto, Ben D.J.; Gill, Sandeep; Sem, Matthew; Macpherson, Alison K.; Hynes, Loriann M.
Abstract: Background: Changes in sternocleidomastoid (SCM) muscle cross-sectional area (CSA) and volume may contribute to neck-related concussion symptoms and whiplash-associated disorders. Magnetic resonance imaging (MRI) data on healthy SCM morphology can provide information that may lead to targeted treatment protocols. Objectives: To examine sex-related differences in MRI-based SCM CSA, SCM volume and neck area in healthy young adults, to analyze associations between measurements and participant variables and to assess inter-rater reliability for measurement quantification. Design: Cross-sectional study. Methods: 13 males and 14 females underwent MRI scans. Slices obtained from C3–C7 were analyzed by three raters. SCM CSA at C4, total SCM volume from C3–C7 and neck area at C4 were quantified. Measurements were calculated as absolute and normalized values by body mass. Multivariable regression was used to analyze associations between normalized measurement values and participant variables. Inter-rater reliability was determined using intraclass correlation coefficients (ICC). Results: Females had significantly lower normalized overall average SCM CSA (mean difference 1.3 mm 2 /kg (95% CI 0.4–2.2, p  = 0.006) and total SCM volume (mean difference 140.8 mm3/kg (95% CI 66.1–215.5, p  < 0.001) than males. Regression models indicated female sex was associated with lower normalized overall average SCM CSA ( p  = 0.004) and total SCM volume ( p  < 0.001). Inter-rater reliability was excellent for SCM CSA (ICC3, 3  = 0.909), SCM volume (ICC3, 3  = 0.910) and neck area (ICC3, 3  = 0.995). Conclusions: These results enhance our understanding of sex-related differences in SCM morphology and will inform future research and clinical practice related to cervical muscle injury. Highlights: MRI measurements of SCM muscle morphology were collected from healthy young adults. SCM muscle CSA (C4), total SCM volume (C3–C7) and neck area C4 were quantified. Females had significantly lower normalized SCM muscle CSA and volume than males. Neck area measurements were similar between sexes when normalized by body mass. Inter-rater reliability for SCM CSA, SCM volume and neck area were excellent.